SOCIAL CRITICAL REVIEW OF ISLAMIC EDUCATION BASED ON LOCAL WISDOM VALUES - Dewi Shara Dalimunthe; Roslina Siregar (IAIN Padangsidimpuan, 2023)
AbstractWriting this journal aims to find out that the process of Islamic education cannot be carried out uniformly but must understand the cultural context from the results of the identification of local cultural treasures as social institutions that functionally act as a set of problem-solving techniques that are passed down as culture from one generation to the next. This research method is a research library using descriptive analysis. The results of this study indicate that Islamic education based on local wisdom is one of the strategies for building the Indonesian nation's civility with the values of wise practices. In a conception of Western philosophical values, the terms altruism and hard work are known.